PROMOSI KESEHATAN MENGGUNAKAN MEDIA BOOKLET TERHADAP PERAN SUAM MENDAMPINGI PERSALINAN DI PMB MEGAWATI - Veradilla; Rohani; Lusi Afriyani (LPPM STIKes Mitra Adiguna, 2023)
Efforts to accelerate the decline in MMR can be done by ensuring that all mothers have access to quality maternal health services. The design of this study used a quasi-experimental design with one group pre-test and post-test design with a total of 30 respondents. The results showed that the average (mean) level of husband's participation before being given a booklet was 1.27 with a standard deviation of 4.45, while the average (mean) level of husband's participation after being given a media booklet with a standard deviation of 2.27, thus there is a decrease in husband's participation with a difference in the average value (mean) of 2.27-1.27 = 1. Statistical test results the p value = 0.000 < 0.05 means that there is an effect of booklet media on the husband's participation in PMB Midwife Megawati in Palembang in 2021. The conclusion of this study shows that there is an effect of health promotion using booklet media on husband's participation in PMB Midwife Megawati in Palembang in 2021. p = 0.003 0.05. It is recommended for health workers to carry out the husband's participation technique in accompanying childbirth